2010
DOI: 10.1002/lary.21009
|View full text |Cite
|
Sign up to set email alerts
|

Association between DNA repair gene ATM polymorphisms and oral cancer susceptibility

Abstract: The ATM rs189037 A allele is correlated with oral cancer susceptibility, and this polymorphism may be a useful marker for oral cancer prevention and early detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 45 publications
(48 reference statements)
4
27
1
Order By: Relevance
“…A remarkable risk was indicated in the nonsmoker subgroup, which is in agreement with major previous studies (Bau et al, 2010;Wang et al, 2011;Liu et al, 2014;Shen et al, 2014). Shen's study also reported that increased risk was associated with ATM-111 (G>A) AA genotype and lung adenocarcinoma in nonsmokers without exposure to cooking oil fumes.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…A remarkable risk was indicated in the nonsmoker subgroup, which is in agreement with major previous studies (Bau et al, 2010;Wang et al, 2011;Liu et al, 2014;Shen et al, 2014). Shen's study also reported that increased risk was associated with ATM-111 (G>A) AA genotype and lung adenocarcinoma in nonsmokers without exposure to cooking oil fumes.…”
Section: Discussionsupporting
confidence: 92%
“…The results suggested that carrying at least one A allele, especially ATM-111 (G>A) AA genotype, significantly increased the susceptibility to overall cancer, which is similar to the conclusion of individual case-control studies (Bau et al, 2010;Wang et al, 2011;Liu et al, 2014).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…This is the first study to reveal an interaction between MMP1 1607 genotype and cigarette smoking on the susceptibility to oral cancer. Long-term tobacco smoking and areca chewing have been shown to contribute to etiology of oral cancer development (9,10,(41)(42)(43)(44). The results showed that gene-environment interaction was not obvious between MMP-8 genotypes and personal risk behaviors, alcohol drinking, cigarette smoking or areca chewing.…”
Section: Discussionmentioning
confidence: 99%
“…Asian population [122]. Promoter hypermethylation of ATM has been linked with early age of onset and poor prognosis in one mixed subsite study [123], however this has not been reproduced in a large oral cavity cancer series [124].…”
Section: (B) the Dna Damage Responsementioning
confidence: 99%